2018
DOI: 10.1111/1759-7714.12759
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nivolumab in non‐small cell lung cancer with preexisting interstitial lung disease

Abstract: BackgroundThe risk of developing lung cancer is high in patients with interstitial lung disease (ILD), as few treatment options are available. Immune checkpoint inhibitors (ICI) are used for the treatment of non‐small cell lung cancer (NSCLC) in clinical practice; however, in patients with preexisting ILD, the risk of ICI‐related pneumonitis is unknown. We evaluated the efficacy and lung toxicity of nivolumab in patients with NSCLC and ILD.MethodsWe retrospectively reviewed the medical records of 216 NSCLC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
121
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 38 publications
(113 reference statements)
6
121
1
Order By: Relevance
“…In our study, none of the patients with preexisting ILD experienced ILD‐AEs or pneumonitis, although the number of the patients was small (n = 6). PFS did not differ significantly between patients with and without ILD (not reached vs 2.56 months, P = .248), consistent with previous studies …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, none of the patients with preexisting ILD experienced ILD‐AEs or pneumonitis, although the number of the patients was small (n = 6). PFS did not differ significantly between patients with and without ILD (not reached vs 2.56 months, P = .248), consistent with previous studies …”
Section: Discussionsupporting
confidence: 91%
“…Only a few retrospective studies reporting the clinical use of ICIs in NSCLC patients with ILD are available. One retrospective study indicated that ICI‐associated pneumonitis was more common in ILD NSCLC patients than in non‐ILD NSCLC patients (31% vs 12%) . In another study, pneumonitis was observed more frequently in patients with preexisting ILD than in those without, but the difference was not statistically significant (29% vs 11%, P = .08) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kanai et al . also showed that the incidence and severity of ILD were significantly higher in those with pre‐existing IP . Therefore, further careful monitoring for ILD is needed during ICI treatment in patients with pre‐existing IP.Recently, Tanaka et al .…”
Section: Discussionmentioning
confidence: 99%